NON-VERBAL DAKWAH COMMUNICATION MODEL IN THE USE OF SIGN-LANGUAGE - Febri Ana Nurfanisa; Abdul Muhid; M. Syukur Ifansyah; Ummi Aidah; Nurhalimatus (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Not all individuals with disabilities experience limitations; in fact, many of those around us possess exceptional talents and abilities, sometimes surpassing those of individuals without disabilities. One illustrative example is Ning Deyiez, who has garnered attention through her advocacy efforts. She seamlessly combines sign[1]language communication with the courage to promote and uphold the Islamic faith. The author intends to conduct a direct observation of Ning Deyiez's advocacy activities with the aim of gaining a deeper understanding. This observation will be supplemented by interviews with interpreters, the research subjects themselves, and the fellow advocates who regularly participate in these weekly activities. Keywords: Da'wah, Sign-Language, Non-Verbal Communication.